A Study on the Effectiveness of Flexible Working Hours in Enhancing Employee Job Satisfaction at ICICI Bank - Durge, Priti Laxmanrao; Tekade, Atul B. (Journal of Neonatal Surgery, 2025)
Flexible working hours have emerged as a pivotal element in contemporary workplace dynamics, particularly in the banking sector, where employee satisfaction significantly influences organizational success. This study delves into the effectiveness of flexible working hours in enhancing job satisfaction among employees at ICICI Bank. Employing a mixed-methods approach, data was gathered through structured questionnaires and in-depth interviews with a diverse group of employees. The findings underscore the positive correlation between flexible schedules and various dimensions of job satisfaction, including work-life balance, stress reduction, and overall productivity. Additionally, the study highlights the critical role of managerial support and policy implementation in fostering a flexible working environment that meets the needs of both employees and organizational goals. Challenges such as coordination issues and fairness in policy application were also analysed to provide a comprehensive perspective. Insights from this research offer valuable implications for human resource strategies, emphasizing that well-structured flexible work arrangements not only enhance employee morale but also contribute to organizational resilience and adaptability in a competitive landscape. By addressing key factors influencing employee preferences and organizational objectives, the study provides actionable recommendations for the banking industry to integrate flexibility as a core component of workforce management.